Impedimetric humidity sensor based on ?-Fe2O3 nanoparticles - Patil, U. V.; Rout, C. S.; Late, Dattatray J. (Advanced Device Materials, 2015)
Humidity sensing characteristics of thick-film sensors based on α-Fe2O3 nanoparticles synthesized by hydrothermal method have been reported. The as-synthesized α-Fe2O3 nanoparticles were characterized by using XRD, Raman spectroscopy, TEM and HRTEM. Our TEM result depicts that the size of α-Fe2O3 nanoparticles were in the range of 20–30 nm with highly crystalline nature. For humidity sensing experiment, the sensitivity of our α-Fe2O3 nanoparticles-based sensor device was found to be ∼99% and the fastest response times were noted, which indicate that the α-Fe2O3 nanoparticle-based humidity sensor device has more future prospects and demand. The humidity sensing properties of α-Fe2O3 nanoparticles seem to be associated to the sorption sites for the water molecules at the nanoparticles interfaces.

Perspective on atomically thin 2d inorganic layered materials for biosensor - Late, Dattatray J.; Rout, C. S.; Chakravarty, Disha; Ratha, S. (Journal of Nanomedicine Research, 2015)

Atomically thin WS2 nanosheets based gas sensor - Late, D. J.; Kanawade, R. V.; Kannan, P. K.; Rout, C. S. (Sensor Letters, 2016)
We report here the UV light and NO2 gas sensing properties of atomically thin few-layered WS2 nanosheets synthesized by a simple hydrothermal method. For the UV sensor, the response time was observed to be <15 s whereas the recovery time was <56 s. The Few layered WS2 nanosheets sensor devices were also tested for different concentration of NO2 gas at room temperature and 100 °C. The response time was observed to be <60 s whereas recovery time was >10 min. Further, the response and recovery time can be shortened by UV illumination or by removing the absorbed gas by heating the device at higher temperature. Our results open up the new avenues for gas sensors based on two-dimensional inorganic layered materials.

Electrodeposited nickel cobalt manganese based mixed sulfide nanosheets for high performance supercapacitor application - Sahoo, S.; Mondal, R.; Late, D. J.; Rout, C. S. (Microporous and Mesoporous Materials, 2017)
Porous multi component Nickel Cobalt Manganese Sulfide (NCMS) nanosheets have been grown on Ni foam by cathodic electrodeposition method. The as-prepared NCMS nanosheets sample is used as an electrode material for supercapacitor application due to its large electrochemically active surface and high porosity structure. Moreover, NCMS nanosheets have good electrical and mechanical connections to the conductive Ni foam to achieve enhanced reaction kinetics with improved electrode integrity. The NCMS nanosheets exhibit an ultrahigh specific capacitance of 2717 Fig at a current density of 1 Aug with excellent cyclic stability and energy density of 94.07 Wh/kg. The electrodeposited NCMS nanosheets with extraordinary electrochemical performance enable the novel electrodes to hold great potential for high efficient energy storage systems.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, P. K. (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of α and β-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of β-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of α and β-NiMoO4 at a base pressure of ∼1 × 10−8 mbar. The obtained turn-on field at emission current density of 1 μA/cm2 for β-NiMoO4 nanosheets and α −NiMoO4 is 1.3 V/μm and 2.2 V/μm respectively were observed. The maximum field emission current density of 1.006 mA/cm2at an applied electric field of 2.7 V/μm was achieved for β-NiMoO4 nanosheets. Furthermore, we found that the β-NiMoO4 nanosheets possess good field emission performance compared to α-NiMoO4. The results indicate that NiMoO4can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase.
Keywords: Current stability; field emission; nanosheets; NiMoO4

VSe2-reduced graphene oxide as efficient cathode material for field emission - Ratha, S. (Journal of Physics and Chemistry of Solids, 2019)
Field emission properties of pristine VSe2 and its hybrid with reduced graphene oxide (RGO) have been investigated in detail. Promising field emission performance were noted with lower values of turn-on and threshold fields of ∼1.3 V μm−1 and 2.12 V μm−1 respectively for the VSe2/RGO hybrid which is much more superior than that of pristine VSe2 emitter and other 2D materials. Density Functional Theory (DFT) simulations have also been performed to qualitatively support our experimental observations through demonstration of Density of States and computation of work function for pristine VSe2 and hybrid VSe2/RGO. The lowering of work function and appearance of additional states near Fermi level from carbon p orbital of RGO is responsible for superior field emission characteristics in hybrid VSe2/RGO compared to pristine VSe2 which supports our experimental observations. Our experimental data and theoretical insight from electronic structure simulations strongly infer that the synthesized hybrid VSe2/RGO has the potential to be tailored as efficient and high performance cathode material in field emission based devices.
Keywords: cathode material; Chalcogenide; Density functional theory; field emission; Vanadium diselenide; Work function